Chapter 11 Watchful Waiting Temporalities of crisis and care in the UK National Health Service - Baraitser, Lisa (Oxford University Press, 2021)
This paper opens up the relationship between vulnerability and the temporalities of care. It takes 'care' as not just a material practice that supports, manages and sustains vulnerable bodies, but as a temporal practice, one that produces time in situations that are otherwise felt to be stuck or 'chronic'. It draws on some co-written anecdotes about the use of 'watchful waiting' by medical practitioners working in general practice in the UK's National Health System (NHS) to think through the meanings of waiting in relation to chronic health and mental health crises. The offer of 'watchful waiting' as a response to 'chronic crisis' becomes a test case for understanding a more general condition of watchful waiting as a form of care, in a context in which waiting for healthcare has become an agony for many, experienced as a form of abandonment or a key sign of health service failure. The paper attempts to re-think 'waiting times' within a wider history of the temporalities of care, in order to elucidate the ways an offer of waiting can itself be understood as a response to vulnerability through a practice of staying with or alongside the chronic temporalities of others.